Involvement of p38 MAPK in Leydig cell aging and age-related decline in testosterone - Luo, Dandan; Qi, Xiangyu; Xu, Xiaoqin; Yang, Leilei; Yu, Chunxiao; Guan, Qingbo (Frontiers in Endocrinology, 2023)
Introduction Age-related decline in testosterone is associated with Leydig cell aging with impaired testosterone synthesis in aging. Obesity accelerates the age-related decline in testosterone. However, the mechanisms underlying the Leydig cell aging and the effects of obesity on Leydig cell aging remain unclear. Method Natural aging mice and diet-induced obese mice were used to assess the process of testicular Leydig cell senescence with age or obesity. Bioinformatic analysis of the young and aged human testes was used to explore key genes related Leydig cell aging. Leydig cell-specific p38 MAPK knockout (p38LCKO) mice were used to further analyze the roles of p38 MAPK in Leydig cell aging. The levels of testosterone and steroidogenic enzymes, activity of p38 MAPK, aging status of Leydig cells, and oxidative stress and inflammation of testes or Leydig cells were detected by ELISA, immunoblotting, immunofluorescence, and senescence-associated β-galactosidase (SA-β-Gal) staining analysis, respectively. Result The serum testosterone level was significantly reduced in aged mice compared with young mice. In the testis of aged mice, the reduced mRNA and protein levels of LHCGR, SRB1, StAR, CYP11A1, and CYP17A1 and the elevated oxidative stress and inflammation were observed. KEGG analysis showed that MAPK pathway was changed in aged Leydig cells, and immunoblotting displayed that p38 MAPK was activated in aged Leydig cells. The intensity of SA-β-Gal staining on Leydig cells and the number of p21-postive Leydig cells in aged mice were more than those of young mice. Similar to aged mice, the testosterone-related indexes decreased, and the age-related indexes increased in the testicular Leydig cells of high fat diet (HFD) mice. Aged p38LCKO mice had higher levels of testosterone and steroidogenic enzymes than those of age-matched wild-type (WT) littermates, with reduced the intensity of SA-β-Gal staining and the expression of p21 protein. Conclusion Our study suggested that obesity was an important risk factor for Leydig cell aging. p38 MAPK was involved in Leydig cell aging induced by age and obesity. The inhibition of p38 MAPK could delay Leydig cell aging and alleviate decline in testosterone.